Evaluation of Antidiabetic Potential (α-Glucosidase and α-Amylase Enzyme Inhibition Assay) of Mundu Leaf Extract [Garcinia dulcis (Roxb.) Kurz] - Novandi Purba; Nur Ulina M. Br Turnip; Jhon Patar Sinurat (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Diabetes Mellitus (DM) is a chronic disease that requires appropriate solutions for its management. To date, synthetic antidiabetic drugs frequently cause side effects in the body. The search for natural antidiabetic agents has therefore been carried out by exploring the potential of mundu leaves, which are considered safer as they originate from natural sources. Mundu leaves contain flavonoids, phenols, and tannins, which may act as natural antidiabetic agents due to their richness in hydroxyl and aromatic compounds. Antioxidant compounds play a role in protecting body cells from oxidative stress, which is strongly associated with diabetes. Several species from the Garcinia genus have been studied, but to date, no research has focused on the antidiabetic potential of mundu leaves. Through assays of mundu leaf extract in inhibiting α-amylase and α-glucosidase enzymes, as well as antioxidant tests, DM could potentially be better controlled, providing a reference for its use as a natural antidiabetic and antioxidant agent. Mundu leaves were prepared and macerated using ethanol as a solvent, followed by evaporation with a rotary evaporator. Phytochemical screening was conducted to detect the presence of active compounds. The inhibitory activity of mundu leaf extract against α-glucosidase and α-amylase enzymes was measured using a UV-Visible spectrophotometer to obtain absorbance values. The absorbance data were then used to determine the percentage of inhibition, allowing the calculation of IC50 values as a benchmark for antidiabetic activity. The results demonstrated that the mundu leaf extract exhibited antidiabetic properties, with IC50 values of 51.058 ppm and 33.004 ppm, categorized as strong and very strong, respectively.